PENGARUH CELEBRITY ENDORSER DAN KUALITAS PRODUK TERHADAP MINAT BELI PRODUK SCARLETT WHITENING - Erica Yusy Fernandi; Siti Ning Farida (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The current modern trend is to use celebrities in order to market their products, namely by using Celebrity Endorsers and also maintaining product quality in order to maintain their superior products. This study aims to determine and analyze the effect of Celebrity Endorsee and Product Quality on Impulse Purchase Interest of Scarlett product consumers. This type of research is descriptive analysis using multiple linear regression analysis. The sampling technique used is non-probability sampling with a purposive sampling approach. The data collection method used in this study is to use a questionnaire that uses a Likert scale. The sample in this study was 100 respondents. Hypothesis testing uses F test for simultaneous test and t test to test the relationship partially. The results of this study indicate that simultaneously, the Celebrity Endorser variable and product quality have a positive and significant effect on buying interest. Partially, the celebrity endorsee variable has a significant and significant effect on buying interest and the product quality variable also has a significant and significant effect on buying interest.